Multifaceted applications of micro/nanorobots in pharmaceutical drug delivery systems: a comprehensive review - Tanisha Das; Shirin Sultana (SpringerOpen, 2024)
Abstract Background Drug delivery systems (DDSs) encompass a wide range of methods, including oral, injectable, and topical routes of administration, all tailored to meet specific patient needs. Micro and nanorobots, equipped with pioneering propulsion mechanisms that convert external energy sources into precise movements, have revolutionized drug delivery. This cutting-edge technology ensures highly efficient drug delivery, particularly when targeting specific targets within intricate physiological environments. In contrast to traditional drug delivery approaches that rely on bloodstream circulation, engineered micro/nanorobots have autonomous mobility, enabling drug delivery to previously unreachable areas. Main body of the abstract Integrating micro/nanorobots into drug delivery raises vital safety and biocompatibility issues. These encompass material selection, degradation in-vivo, overcoming biological barriers, controlled movement, external interference, immune response, chemical reactions, systemic effects, long-term impact, and real-time monitoring. While micro/nanorobots hold immense transformative potential, they confront significant hurdles in their journey toward practical applications. Chief among these challenges are concerns regarding biocompatibility, ensuring that these tiny devices do not trigger adverse reactions. Long-term safety remains a critical issue, as understanding the effects of prolonged exposure and potential accumulations within the body and navigating complex biological environments with precision is another obstacle. Short conclusion The paper summarizes how to explore the various ways in which micro/nanorobots can be employed to enhance drug delivery, including their precision, targeting capabilities, and adaptability to different physiological conditions. Additionally, the review seeks to highlight the transformative potential of these technologies and their impact on the pharmaceutical industry.